Assessment of Bacterial Contamination and Antibiotic Susceptibility Patterns of Bacteria Isolated from Milk collected from Biharwe in Mbarara District: Cross-Sectional Study - Mugenyi, Nathan; Amanya, Martin; Ssebagala, Pius Stewart; Kisembo, Desire; Joseph, Fortunate Kabuuye; Ninsiima, Prize (Journal of Veterinary Medicine and Surgery, 2022)
Milk and dairy products are important source of vital nutrients for human beings. The unique composition and properties make milk an excellent medium for bacterial growth and source of bacterial infection. Milk borne pathogenic bacteria pose a serious threat to human health, and constitute about 90% of all dairy related diseases. Staphylococcus aureus, Salmonella spp., and Listeria monocytogenes, Escherichia coli O157:H7 and Campylobacter are the main microbiological hazards associated with raw milk consumption. Microbiological status of raw milk is affected by several factors including a health status of the animal, farm management practices, environmental hygiene and poor temperature control. In some countries with low socioeconomic status, income growth and urbanization has led to almost doubled consumption of milk and dairy products [1-4]. Unlike in developed countries, the dairy industry in most African countries is underdeveloped, dominated by unpasteurized milk and informal markets.
Keywords: Pathogens; Cow’s milk; E. coli; Tetracycline; Contamination